Enterprise risk management manufacturing industry quality determinants: Malaysia and Indonesia context - Dhewi, Ratna Marta; Martunus, Hendrian; Hidayah, Nurul; Setiany, Erna (Brazilian Journal of Operations & Production Management, 2025)
Goal: Large manufacturing companies face significant risks due to importing raw materials and exposure to fluctuating exchange rates. Enterprise Risk Management (ERM) is vital in this sector to manage its distinctive risks. This study finds ERM factors in Indonesia and Malaysia that affect company value and empirically evaluates risk management in their organizations. Design / Methodology / Approach: The factors that influence the quality of a company's ERM examined in this study include auditor quality, ownership concentration, board monitoring, gender on the board of commissioners, gender on the board of directors, and human capital. This study's population is 2018-2020; 300 Indonesian and 252 Malaysian manufacturing companies contributed 552 research observations. Results: This study shows that a qualified auditor, board monitoring, gender ratio on the board of commissioners, and human capital may uncover ERM implementation issues. On the other hand, higher share ownership does not affect ERM. Implications for practitioners and suggestions for future researchers are also described. Limitations of investigation: The crucial role of Enterprise Risk Management (ERM) in mitigating these unique industry risks, this study underscores the limitations inherent in factors such as auditor quality, ownership concentration, board monitoring, and gender diversity within corporate leadership. Practical implication: The necessity for manufacturing companies to prioritize specific aspects of Enterprise Risk Management (ERM) in their organizational strategies. Originality / Value: This research illuminates the nuanced interplay of factors shaping Enterprise Risk Management (ERM) efficacy within the dynamic context of the manufacturing industry.